Synthesis, spectral characterization and some biological studies of transition metal complexes with Schiff base ligand containing N,O and S as donor atoms - M R, Anil Kumar; S, Shanmukhappa; B E, Rangaswamy; M, Revanasiddappa (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Transition metal complexes of Cu(II), Co(II), Ni(II), Zn(II), Cd(II) and Mn(II) have been synthesized with the Schiff base ligand 5-Sub-N-(2-mercaptophenyl)salicylideneimine. Elemental analysis of these complexes suggest that these metal ions forms complexes of type ML(H2O)stoichiometry for Cu(II), Co(II), Ni(II), Zn(II), Cd(II) and Mn(II). The ligand behaves as tridentate and forms coordinate bonds through O, S and N atoms. Magnetic susceptibility, IR, UV – Visible, Mass and ESR spectral studies suggest that Cu(II), Ni(II) complexes posses square planar geometry, whereas Co(II), Zn(II), Cd(II) and Mn(II) complexes posses tetrahedral geometry. The complexes were tested for their antimicrobial activity against the bacterial strains Staphylococcus aureus and Bacillus subtilis.The Schiff base metal complexes evaluated for their antifungal activity against the fungi A. niger and C. oxysporum. The DNA cleavage studies of Schiff base complexes werestudied using Calf – Thymus DNA by agarose gel electrophoresis method.